Somatosensory profiles in acute herpes zoster and predictors of postherpetic neuralgia - Kramer, Sybille; Treede, Rolf-Detlef (Pain, 2019)
This prospective cohort study aimed to characterize the sensory profile during acute herpes zoster (AHZ) and to explore sensory signs as well as physical and psychosocial health as predictors for postherpetic neuralgia (PHN). Results of quantitative sensory testing of 74 patients with AHZ at the affected site and at the distant contralateral control site were compared to a healthy control group. Pain characteristics (Neuropathic Pain and Symptom Inventory and SES), physical functioning, and psychosocial health aspects (Pain Disability Index, SF-36, and STAI) were assessed by questionnaires. Patients with PHN (n = 13) at 6-month follow-up were compared to those without PHN (n = 45). Sensory signs at the affected site were thermal and vibratory hypesthesia, dynamic mechanical allodynia (DMA), pressure hyperalgesia, and high wind-up (18%-29%), as well as paradoxical heat sensations and pinprick hypalgesia (13.5%). The unaffected control site exhibited thermal and vibratory hypesthesia, DMA, and pressure hyperalgesia. Dynamic mechanical allodynia and pinprick hypalgesia were mutually exclusive. Postherpetic neuralgia was associated with DMA (38.5% vs 6.7%; P = 0.010) and vibratory hypesthesia (38.5% vs 11.1%; P = 0.036) at the control site, with mechanical gain and/or loss combined with normal thermal detection (affected site: 69.2% vs 31.1%; P = 0.023; control site: 53.8% vs 15.5%; P = 0.009). Pain Disability Index (P = 0.036) and SES affective pain perception scores (P = 0.031) were over 50% higher, and 6 of 8 SF-36 subscores were over 50% lower (P < 0.045) in PHN. Sensory profiles in AHZ indicate deafferentation and central but not peripheral sensitization. Sensory signs at distant body sites, strong affective pain perception, as well as reduced quality of life and physical functioning in the acute phase may reflect risk factors for the transition to PHN.